The Contribution of Environmental and Social Standards Towards Ensuring Legitimacy in Supply Chain Governance - Mueller, Martin (Journal of business ethics, 2009)
Increasingly, companies implement social and environmental standards as instruments towards corporate social responsibility (CSR) in supply chains. This is based on the assumption that such standards increase legitimacy among stakeholders. Yet, a wide variety of standards with different requirement levels exist and companies might tend to introduce the ones with low exigencies, using them as a legitimacy front. This strategy jeopardizes the reputation of social and environmental standards among stakeholders and their long-term trust in these instruments of CSR, meaning that all expenses for their implementation are of no avail for the companies. Therefore, this paper highlights which criteria are important for the selection, implementation and improvement in order to achieve a company's aim, but also to strengthen the legitimacy of social and environmental standards. This research is based on conceptual thought and some existing empirical research, comparing four different social and environmental standards, revealing weaknesses and strengths. It exposes the basic conditions for the success of such standards among stakeholders and identifies the need for more empirical data.